An efficient routing scheme to reduce packet loss in all optical networks - Garg,Amit Kumar (2010)
Optical burst switching (OBS) is a promising technology for the next generation optical Internet. A buffer-less OBS network can be implemented using ordinary optical communication equipment without the need for either wavelength converters or optical memories. However, OBS networks suffer from a relatively high blocking probability, a primary metric of interest, because of contention. In this paper, an efficient deflection routing scheme for buffer-less OBS networks has been proposed in order to reduce blocking probability (Packet loss) caused by Offset Time (OT) and burst contention. Simulation results have shown that the proposed scheme reduces blocking probability effectively and also it maintains a reasonable end-to-end delay for each burst. Thus, it improves the overall network performance by reducing the burst blocking probability effectively.